Kinetics and Mechanism of Oxidation of Cinnamaldehyde by Chromium(VI) - Chellamani, A.; Alhaji, N.M.I.; Selvarajan, S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of cinnamaldehyde by Cr(VI) in 90% (v/v) aqueous acetic acid has been studied. The reaction follows second-order kinetics, first-order each in cinnamaldehyde and Cr(VI), at constant ionic strength and [H+]. A mechanism involving the chromic acid ester of hydrated cinnamaldehyde as intermediate has been suggested.